Underwater acoustic physical layer emulator to evaluate digital communication - Martins, Marcos Silva (2016)
In order to achieve underwater acoustic high data-rate and real time communications, it is essential to implement a system that operates both at high and wideband frequencies using digital modulations. Therefore, to reduce the time and cost of developing acoustic communications an emulator of a physical layer model was implemented, allowing to test in real time the performance of digital modulations. The model was composed of an emitter transducer, a hydrophone and the subaquatic medium and was integrated in a Field Programmable Gate Array (FPGA) in order to emulate the physical layer in the acoustic modem testing. The emitter transducer and the hydrophone models were designed to meet real prototype characteristics. The system prototype was implemented in order to compare the experimental trials results with those obtained in emulator, emulating the transmission of acoustic signals, using different types of digital modulations. The system was tested using Binary Phase-Shift Keying (BPSK), Binary Frequency Shift keying (BFSK) and Binary Amplitude Shift Keying (BASK) modulations with a 1 MHz carrier frequency resulting in a data rate of 125 kbps. It was verified that the implemented model represents a suitable approximation to the real subaquatic communication channel, allowing the evaluation of digital acoustic communications.